Design and Implementation of a Robotic Arm Controlled By an Arduino - Bekakra Mohmmed elBachir; Gaid Oussama; Radouni Abderraouf (University of Shahid Hama Lakhdar - El Oued, 2024)
The use of manipulator robots is an industry standard for automating production lines. These robots are precise, robust and fast. To achieve their performance, they are designed with powerful actuators and they are made of massive parts. Several strategies such as the use of control algorithms and mechanical designs are used to reduce the danger of a robot manipulator and as well as improving its performance for users. This dissertation aims to study, through simulation and practical implementation, the design of a robotic arm manipulator with three degrees of freedom.يعد استخدام الروبوتات المناولة معيارًا صناعيًا لأتمتة خطوط الإنتاج. هذه الروبوتات دقيقة وقوية وسريعة. لتحقيق أدائها، تم تصميمها بمحركات قوية وهي مصنوعة من أجزاء ضخمة. يتم استخدام العديد من الاستراتيجيات مثل استخدام خوارزميات التحكم والتصميمات الميكانيكية لتقليل خطر مناور الروبوت وتحسين أدائه للمستخدم. تهدف هذه الأطروحة إلى دراسة تصميم مناور ذراع آلي بثلاث درجات من الحرية من خلال المحاكاة والتنفيذ العملي.
Master's thesis in electromechanics
Keywords: Robotics; Robots; Manipulator robots; Design; Simulation; الروبوتات، الروبوتات، الروبوتات المتلاعبة، التصميم، المحاكاة.